Conjoint analysis of methylation, transcriptomic, and proteomic profiles in pemphigus vulgaris - Xiaojia Luo; Jianting Ouyang; Fuqiong Jiang; Yaozhong Zhang; Yuan Wang; Yongzhuo Wu; Lingyu Hu (Orphanet Journal of Rare Diseases)
Abstract Background The underlying pathogenesis of pemphigus vulgaris, an autoimmune skin disorder, remains incompletely understood. An integrative analysis comprising DNA methylation, mRNA expression, and proteomic data in patients with pemphigus vulgaris was conducted to identify potential pathogenic contributors and explore the molecular mechanisms involved in its pathogenesis. Results The analysis revealed differentially methylated regions (DMRs) in the promoter, exon, intron, and downstream regions in the peripheral blood DNA of patients with pemphigus vulgaris. Associations between methylation levels and both transcriptomic and proteomic profiles revealed that differentially expressed genes between patients with pemphigus vulgaris and healthy controls were primarily linked to biological functions such as platelet activation and coagulation, cellular adhesion, and immunoglobulin binding. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis highlighted notable pathway abnormalities, including those related to platelet activation, focal adhesions, tight junctions, and infectious inflammatory responses. Notably, genes such as FGA (fibrinogen alpha chain), VWF (von Willebrand factor), and ACTG1 (actin gamma 1) were dysregulated, with a prominent role in platelet activation. Conclusion The dysregulation of genes such as FGA, VWF, and ACTG1 suggests that alterations in their transcription and expression may contribute to the pathogenesis of pemphigus vulgaris.